Análise quantitativa e qualitativa do descomissionamento do sistema submarino de um campo petrolífero - Borges, Priscilla Rangel (2018)
An oil field after its productive life has ended, reaches a phase called abandonment or decommissioning. With regard to subsea production equipment, this occurs when the activity is disadvantageous and / or its life cycle reaches the limit, and then production is finalized to accomplish with cleaning, equipment removal and environmental recovery of the explored region. This activity comprises operations of high cost and high potential of occurrence of environmental impacts. Decommissioning is a multidisciplinary activity, since environmental, social, technical, economic and safety criteria should be considered in its planning, making it important to approach methods that seek a balance between these aspects. Therefore, multicriteria analysis tools should be used as an aid to decision making. In this work, such tools were used to evaluate the best forms of decommissioning of subsea equipment in an ultra deepwater oil field. The work explicited different approaches and made a comparison between them, in order to evaluate which method would more effectively meet the needs of the decision maker.